SISTEM PENUNJANG KEPUTUSAN SISWA BERPRESTASI MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING PADA SMK COKROAMINOTO LUWUK - I Ketut Putra Yasa; Chia Adinda Jamaludin; Naila Tabitai (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
Determining outstanding students at SMK Cokroaminoto Luwuk has been carried out conventionally, so the score recapitulation process takes a long time and is prone to subjectivity. This study aims to build an objective and efficient Decision Support System (DSS) using the Simple Additive Weighting (SAW) method. System development applies the Waterfall model which includes the stages of analysis, design, coding, and testing. The data used include six main criteria: attendance, report card scores, competency tests, school exams, non-academic achievements, and violation levels. The research results show that the developed web-based system is capable of accurately automating normalization and ranking calculations. Functional testing using Black Box Testing confirms that all system features run according to specifications. The implementation of this DSS has succeeded in increasing data processing time efficiency and providing transparency in determining the best students for the school.